Rhizophagus intraradices dan Trichoderma asperellum sebagai Bioprotektan dan Biofertilizer pada Bawang Merah TSS - Puti Maharani; Suryanti Suryanti; Tri Joko; Susamto Somowiyarjo (Jurnal Ilmu Pertanian Indonesia, 2024)
True shallot seed (TSS) is one of the alternative potential technologies to solve the availability of seed quality on shallot in Indonesia. Another problem in shallot production is infection by purple blotch and twisted disease. This research evaluated the potency of Rhizophagus intraradices and Trichoderma asperellum as bioprotectants and biofertilizer. T. asperellum was mixed in the soil before seedling transplanting, and R. intraradices was applied around the seedling roots at transplanting. The observed parameters were the shallot growth (the plant height, number of leaves, and length of root), plant health (disease incidence and intensity), and bulb resistance to Fusarium solani. The result showed that R. intraradices and T. asperellum increased the resistance of onion bulbs to the pathogen F. solani in the postharvest period, indicated by R. intraradices treatment that had an infection area of 21.99 mm2, followed by T. asperellum treatment 26.63 mm2, and control of 37.66 mm2. Keywords: Rhizophagus intraradices, Trichoderma asperellum, true shallot seed